2022
DOI: 10.1088/1361-6463/ac472d
|View full text |Cite
|
Sign up to set email alerts
|

Performance recovery of plasma actuators in wet conditions

Abstract: Plasma actuators have been extensively studied for flow control applications. While these studies have been traditionally focused on characterizing their performances as flow control devices, the performance of plasma actuators under adverse conditions like light rain remains to be less explored. This paper seeks to study the effects of water adhesion from droplets directly sprayed on to a plasma actuator using thrust recovery as the performance metric. It was found in all tests that wet actuators quickly reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…For example, at RH = 75% in figure 8, the maximum number of monolayers is 4, in qualitative agreement with Monte Carlo molecular simulations [43]. This would seem to be much too thin (∼1 nm) to form an electrically-conducting water film; however, even as few as three monolayers (RH > 66%) are, surprisingly, already sufficient to exhibit significant surface electrical conductivity [9,44,45]. The thin film conductivity enhancement factor, relative to bulk water [44], is shown to be as high as 10 5 , and could be due to conduction along a polarized HOHHO − layer, by tunneling via dipole resonances [46].…”
Section: The Possible Physical Origin Of Water Film On the Dielectric...supporting
confidence: 68%
“…For example, at RH = 75% in figure 8, the maximum number of monolayers is 4, in qualitative agreement with Monte Carlo molecular simulations [43]. This would seem to be much too thin (∼1 nm) to form an electrically-conducting water film; however, even as few as three monolayers (RH > 66%) are, surprisingly, already sufficient to exhibit significant surface electrical conductivity [9,44,45]. The thin film conductivity enhancement factor, relative to bulk water [44], is shown to be as high as 10 5 , and could be due to conduction along a polarized HOHHO − layer, by tunneling via dipole resonances [46].…”
Section: The Possible Physical Origin Of Water Film On the Dielectric...supporting
confidence: 68%
“…One of the main reasons for this is the concern over weather conditions such as rain. In this regard, Lilley et al reported that DBDPA is sufficiently durable even when completely wet, and that its performance gradually recovers with continuous actuation in dry air [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study shows the potential of the APS as a sterilization technology for applications in planetary protection with advantages of uniform spatial decontamination, low processing temperatures, low exposure times, lightweight with no moving parts, ability to decontaminate porous surfaces and compatibility with relevant materials. Additionally, it is important to note that the DBD reactors has been successfully tested and found to regain performance even when water droplets are present on the work surface [30] making it a better candidate for a broad range of practical sterilization applications. Future research on the APS is needed for detailed material compatibility studies and further evaluation of the system in sterilizing other species of interest to planetary protection.…”
Section: Discussionmentioning
confidence: 99%